FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi pada Perusahaan LQ 45 yang terdaftar di Bursa Efek Indonesia) - Arifianto, Agil Nur; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of firm size, profitability, leverage, auditor opinion, PAF quality to the audit delay. This research has been conducted by using LQ 45 companies which are listed in Indonesia stock exchange (IDX) in 2011-2015 periods. The research sample has been done by using purposive sampling method at LQ 45 companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods. Based on the predetermined criteria 22 companies have been selected as samples. The analysis method has been conducted by using multiple linear regressions analysis. The result of this research shows that: (1) firm size has negative influence to the audit delay because when the firm size is high, it will shorten the audit delay. (2) Profitability has positive influence to the audit delay because when the profit is highit will cause the checking process becomes wide and carefully. (3) Leverage has negative influence to the audit delay because high debt the company will publish its financial statement to minimize risk in capital return. (4) Auditors opinion does not have any influence to the audit delay because issuing an opinion to the financial statement is the final steps of audit process. (5) The PAF quality does not have any influence to the audit delay because the big four do not give any guarantee of the occurrence of timelinessof the submission of the financial statement.Keywords: Audit delay, firm size, profitability, leverage, Public Accountant Firm quality.